Polygalacturonase activity in starfruit - Ghazali, H.M.; Leong, C.K. (Elsevier, 1987)
Polygalacturonase (PGase) was extracted and partially purified from ripe starfruit (Averrhoa carambola, L.). 2·3- and 7·8-fold purifications were obtained following purification by Amicon ultrafiltration and Sephadex G-100 filtration, respectively. The apparent pH optimum of PGase in the Amicon concentrate and gel filtrate (combined fractions 6-8) was 5·2. Viscometric and reductometric analyses, on PGase in the gel filtrate and paper chromatographic analysis on the enzyme reaction mixture, were carried out to ascertain the mode of action. The results obtained indicated that exoPGase was the only PGase enzyme present in ripe starfruit.